Peer Teaching dalam Pembelajaran Sejarah Kebudayaan Islam Masa Pandemi Covid 19 di MA Al-Urwatul Wutsqo Diwek Jombang - Ali Mustofa (Attanwir : Jurnal Keislaman dan Pendidikan, 2022)
Thelearning method peer teaching during a pandemic is very effective, it is an alternative that can be used by teachers because it has high dynamics of motivation so that it is expected to increase student learning motivation. Students do not meet the teacher but meet their peers at home. The results of the study stated, 1). SKI learning planning, namely the teacher designs the material that is conveyed, determines peer tutors, trains peer tutors, 2). Implementation of peer teaching at MA Al-Urwatul Wutsqo, teachers form groups, peer tutors explain the material, teachers supervise the learning process. 3). Evaluation of peer teaching at MA Al-Urwatul Wutsqo was carried out in a way, the teacher gave questions, a written evaluation, the teacher assigned to explain the material briefly according to each group. The conclusion of the research onmethods peer teaching in learning SKI at MA Al-Urwatul Wutsqo states 1). Planning is designing the material that is delivered, determining peer tutors, training peer tutors. 2). Implementation is, the teacher forms groups, peer tutors explain the material and the teacher supervises the learning process. 3). Evaluation is carried out orally, namely the teacher gives questions to students, in writing, namely students summarize or write the material that has been conveyed, students from each group briefly explain the material that has been conveyed, after that the teacher gives homework.